Electrolyte multiplexing in electrochemical jet processing - Mitchell-Smith, Jonathon; Speidel, Alistair; Bisterov, Ivan; Clare, A.T. (Elsevier, 2018)
Electrolyte design for electrochemical jet processing (EJP) techniques can directly affect form and finish of machined structures.